Genesis and Classification of Selected Soils in an Arid Region of Central Iraq. Issue 6 (31st October 2013) - Muhaimeed, A.S.; al‐Jeboory, S.R.; Saliem, K.A.; Burt, R.; Chiaretti, J.V.
Abstract : Five pedons were studied and sampled around Razazah Lake in central Iraq west of the city of Karbala. This lake is a depression into which excess water from the Euphrates River is diverted by a controlled escape channel. Razazah Lake is shallow, and water levels fluctuate seasonally. The climate of the region is hot and arid with mean annual temperature of 22.5°C and mean annual precipitation of 150 mm. The pedons represent gypsiferous and calcareous soils that formed from different parent materials overlying several geological formations and which have different groundwater levels. Soils were described, sampled, and analyzed in USDA–Lincoln laboratory using standard USDA soil survey methods, with some soil properties determined by Iraqi laboratories. The results indicate differences in the morphological, chemical, physical, and mineralogical properties of the pedons. These differences were related to local factors including age and type of their geological formation, topographic location, and depth of groundwater. Presence of groundwater and composition of the geological formations were major factors in the amount, form, and depth of carbonate and gypsum in the pedons. Microscopic gypsum appears as lenticular, granular, and platy forms, either as single grains or as accumulations filling soil voids or coating voids. Four of the five pedons studied classify as Aridisols in U.S. soil taxonomy and have predominately calcic and gypsic diagnostic subsurface horizons.